DISTRIBUSI ZAKAT FITRAH DIANTARA SESAMA SAUDARA KANDUNG DALAM PERSPEKTIF HUKUM ISLAM - Cut Ali, Isnu (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2024)
For Muslims, every time the holy month of Ramadan arrives, they will of course carry out the fasting which is obligatory by Allah SWT as He says in surah Al Baqarah: 183 that every believer is ordered to fast as he has been ordered to people before him to be pious. In the same aspect, Muslims are also ordered to issue zakat fitrah in the holy month of Ramadan as a form of obeying Allah's commands. to become a pious human being. According to the scholars, the law for people who do not issue zakat fitrah can be divided into two groups, namely groups who deny the obligation of zakat fitrah and groups who are reluctant to issue zakat fitrah because they are stingy or miserly. Of course, Muslims who believe in Allah and the hereafter do not want to be included in these two groups because they are afraid of Allah's punishment in their life in this world and in the hereafter. Globally, Muslims around the world do not question differences in legal cases regarding the form of zakat fitrah because this study has an explanation in the scientific literacy of the four schools of fiqhiyah. In it there are two versions which are permissible according to the feasibility and benefit studies, that is, they may be issued in the form of certain principal items or in the form of an equivalent price value. However, basically, zakat fitrah expenditure is more prioritized, namely in the form of rice or other staple foods that are consumed by individuals and communities in a region/country. But there are other things that become a behavior in which Muslims issue their zakat and hand it over to amil zakat in mosques or institutions that are formed to take care of the management and distribution of zakat. On the other hand, Muslims distribute their own zakat fitrah to people who are deemed entitled to receive it, even to their own families and relatives. Phenomena like this are clearly seen everywhere, especially in Indonesia where I myself (the reviewer) live in Keude Aceh Village, Banda Sakti District, Lhokseumawe City, Aceh. Based on the background above, the reviewer conducted research on the theme of the problem raised, namely "Review of Islamic Law in the Distribution of Zakat Fitrah Among Siblings". From this theme the reviewer will focus his research on several problem formulations to obtain relevant answers to the matter being studied.